Spectroscopy essential topics and diverse applications - Penn, Jason (New York, NY, USA NY Research Press, 2015)
This book talks about latest developments in technology, functions and other advancements in spectroscopy. Spectroscopy scientists from various domains had been encouraged to share and discuss information that has been included in this book. With inputs from experts in Chemistry, Biochemistry, Physics, Biology and Nanotechnology, this book is a treasured resource of knowledge for readers. This book will augment the understanding of researchers about complications of different spectroscopic approaches and urge professionals and beginners to contribute part of their future research in understanding relevant mechanisms and applications of chemistry, physics and material sciences. This book focuses on the following sections: atomic absorption spectroscopy, UV-VIS spectroscopy, FT-IR spectroscopy and fluorescence spectroscopy.
Includes bibliographical references.
Keywords: Spectrum analysis -- Research